2017
DOI: 10.2147/ott.s130409
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of mitochondrial serine hydroxyl-methyltransferase 2 is associated with poor prognosis and promotes cell proliferation and invasion in gliomas

Abstract: Mitochondrial serine hydroxyl-methyltransferase 2 (SHMT2), participating in the synthesis of mitochondrial thymidine monophosphate, has been reported to drive glioma cell survival in ischemia. However, its clinical relevance in gliomas remains unclear. In the current study, immunohistochemistry was performed to examine subcellular localization and expression levels of SHMT2 protein in glioma and non-neoplastic brain tissue specimens. Then, the associations of SHMT2 expression with various clinicopathological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
3
27
0
1
Order By: Relevance
“…The one-carbon units result mainly from the activity of serine hydroxymethyltransferases (SHMTs, EC 2.1.2.1), which reversibly interconvert Ser and glycine (Gly). Consistently, an increasing amount of evidence has pinpointed SHMTs as pivotal in highly proliferating cells ( Girgis et al, 1997 ; Townsend et al, 2004 ; Wu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 84%
“…The one-carbon units result mainly from the activity of serine hydroxymethyltransferases (SHMTs, EC 2.1.2.1), which reversibly interconvert Ser and glycine (Gly). Consistently, an increasing amount of evidence has pinpointed SHMTs as pivotal in highly proliferating cells ( Girgis et al, 1997 ; Townsend et al, 2004 ; Wu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 84%
“…At the same time, studies have found that TMPRSS2 cells are a useful experimental system for studying the cleavage and inhibition of HA by host cell proteases. In addition, these cells also represent a suitable cell line for propagation of the influenza virus in the absence of trypsin (Wu et al, 2017). Interestingly, TMPRSS2 can cleave SARS-COV-2 spike protein, thus facilitating viral entry and activation (Hoffmann et al, 2020), which suggest its correlation with SARS-COV-2.…”
mentioning
confidence: 99%
“…SHMT2, located on human chromosome 17, is responsible for encoding the mitochondrial form of a pyridoxal phosphate-dependent enzyme [13]. An important paralog of SHMT is SHMT1, which is mainly present in the cytoplasm [14].…”
Section: Introductionmentioning
confidence: 99%
“…An important paralog of SHMT is SHMT1, which is mainly present in the cytoplasm [14]. SHMT2 is primarily involved in catalyzing the conversion of serine to glycine, and simultaneously transfers b-carbon from serine to hydrolyzed tetrahydro ate (THF) to form 5,10-methylenettrahydrofolate (Me THF) [13,15]. As the hub of serine catabolism and single carbon metabolism, SHMT2 plays a regulatory role, in which small molecular metabolites control cell proliferation [16].…”
Section: Introductionmentioning
confidence: 99%